2021
DOI: 10.1175/jcli-d-20-0417.1
|View full text |Cite
|
Sign up to set email alerts
|

Future Changes in Tropical Cyclone Intensity and Frequency over the Western North Pacific Based on 20-km HiRAM and MRI Models

Abstract: The future changes in the tropical cyclone (TC) intensity and frequency over the western North Pacific (WNP) under global warming remain uncertain. In this study, we investigated such changes using 20-km resolution HiRAM and MRI models, which can realistically simulate the TC activity in the present climate. We found that the mean intensity of TCs in the future (2075−2099) would increase by approximately 15%, along with an eastward shift of TC genesis location in response to the El-Niño like warming. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Observational and modeling evidences of global-warming impacts on TC activities (e.g., TC intensify, frequency, track, moving speed, precipitation, size, etc.) have been better provided, and the physical connection to the global-warming-induced changes in sea surface temperature, ocean heat content, and water vapor concentrations have been widely explored (Chan and Liu 2004;Emanuel 2005;Webster et al 2005;Wu et al 2005;Alexander et al 2006;Klotzbach 2006;Tu et al 2009;Wang et al 2011;Park et al 2014;Chang et al 2013;Knaff et al 2014;Kossin et al 2014;Klotzbach and Landsea 2015;Kossin et al 2016;Mei and Xie 2016;Daloz and Carmargo 2017;Zhan and Wang 2017;Balaguru et al 2018;Leroux et al 2018;Song and Klotzbach, 2018;Bhatia et al 2019;Wang et al 2019;Chih and Wu 2020;Hung et al 2020;Hsu et al 2021;Hong et al 2021;Xiao 2021;Guo and Tan 2022;Li et al 2022;Wang et al 2022;Tian et al 2022). Since the pioneering efforts to develop and deploy GCMs (Smagorinsky et al 1965;Manabe et al 1965) and the simultaneous expansion in computational power, the ability of these models to capture climatological changes has grown considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Observational and modeling evidences of global-warming impacts on TC activities (e.g., TC intensify, frequency, track, moving speed, precipitation, size, etc.) have been better provided, and the physical connection to the global-warming-induced changes in sea surface temperature, ocean heat content, and water vapor concentrations have been widely explored (Chan and Liu 2004;Emanuel 2005;Webster et al 2005;Wu et al 2005;Alexander et al 2006;Klotzbach 2006;Tu et al 2009;Wang et al 2011;Park et al 2014;Chang et al 2013;Knaff et al 2014;Kossin et al 2014;Klotzbach and Landsea 2015;Kossin et al 2016;Mei and Xie 2016;Daloz and Carmargo 2017;Zhan and Wang 2017;Balaguru et al 2018;Leroux et al 2018;Song and Klotzbach, 2018;Bhatia et al 2019;Wang et al 2019;Chih and Wu 2020;Hung et al 2020;Hsu et al 2021;Hong et al 2021;Xiao 2021;Guo and Tan 2022;Li et al 2022;Wang et al 2022;Tian et al 2022). Since the pioneering efforts to develop and deploy GCMs (Smagorinsky et al 1965;Manabe et al 1965) and the simultaneous expansion in computational power, the ability of these models to capture climatological changes has grown considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Although low-resolution global climate models have successfully captured the temporal and geographical distributions of TC activity (Manabe et al 1970;Vitart et al 1997;Camargo et al 2005), their simulations generally underestimate the intensity and rapid intensification of TCs. Studies have reported that this underestimation can be improved considerably by applying high-resolution models (Murakami and Sugi 2010;Camargo 2013;Roberts et al 2020a;Roberts et al 2020b), which are crucial for producing future projection (Murakami et al 2011;Murakami et al 2012;Tsou et al 2016;Roberts et al 2020b;Hong et al 2021;Hsu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Emanuel [10] finds an increase in the global average frequency of tropical cyclones in the range of 10-40% during the first three quarters of the 21st century. Along with the frequency, the average intensity of tropical cyclones is also increasing by ~15% [11]. Shamir et al [12], in their review of current knowledge on climate change trends of precipitation, found that heavy rainfall events are expected to intensify as well as the frequency and intensity of large eastern pacific tropical cyclones.…”
Section: Introductionmentioning
confidence: 99%